Vital signs or flatline? Canadian physical and health education research publication activity. Issue 5 (13th June 2022) - Lorusso, Jenna R.; Schaefer, Lee
ABSTRACT: To inform a response to recent critiques of physical and health education (PHE) research activity within Canadian universities, this research inquired into peer-reviewed PHE publications by Canadian-based authors between 2010 and 2015 via an analysis of published research method framed within a ' health ' metaphor. The three-phase method involved: (a) identifying Canadian-authored English-language PHE journal articles via targeted database keyword searches designed in consultation with an academic librarian and the Physical and Health Education Canada Research Council executive; (b) categorizing the publications by extracting data related to author affiliation, journal name, research question, and funding acknowledgement; and (c) conducting basic descriptive statistics to report findings on publication topics, authorship characteristics, journal outlets, and funding rates and sources. Results were interpreted through the lens of common criteria within Canadian tenure, promotion, and performance reviews for ' healthy ' research publication activity: quantity of publications, prestige of publication outlets, knowledge mobilization to national and international practitioners and academics, and (external) funding. Findings revealed relatively ' healthy ' measures of publication quantity, prestigious external funding, and nationally-focused knowledge mobilization to stakeholders inside and outside of academia. However, findings also revealed limits in the proportion of research published in prestigious journals and journals easily accessible to international audiences, both of which could be interpreted or represented (and subsequently weaponized) by others as ' illness '. While it is neither our aim, nor place, to prescribe a way forward – as that is for the larger community of Canadian-based PHE scholars to consider together – it is our hope that this research provides the descriptive data and reflection needed to inform the beginnings of evidence-based discussion, action, and advocacy regarding PHE research publication activity in Canada.